2015
DOI: 10.1073/pnas.1505512112
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of Yorkie activity by LKB1/AMPK and the Hippo/Warts cascade in the central nervous system

Abstract: The Hippo (Hpo) pathway is a highly conserved tumor suppressor network that restricts developmental tissue growth and regulates stem cell proliferation and differentiation. At the heart of the Hpo pathway is the progrowth transcriptional coactivator Yorkie [Yki–Yes-activated protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ) in mammals]. Yki activity is restricted through phosphorylation by the Hpo/Warts core kinase cascade, but increasing evidence indicates that core kinase-independent mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 105 publications
(125 reference statements)
3
44
0
Order By: Relevance
“…Meanwhile, none of the studies that found a link with AMPK in mammalian systems directly explored its potential regulation by LKB1. However, a recent study in Drosophila observed Yorkie regulation by LKB1 and AMPK: the inactivation of LKB1 in the developing central nervous system induced the activation of Yorkie and a corresponding overgrowth of larval tissues, while LKB1 overexpression induced Yorkie inhibition through AMPK [56]. In line with observations in mammalian systems, AMPK was able to directly phosphorylate Yorkie in vitro.…”
Section: Involvement Of Lkb1: Insights From Drosophilasupporting
confidence: 66%
“…Meanwhile, none of the studies that found a link with AMPK in mammalian systems directly explored its potential regulation by LKB1. However, a recent study in Drosophila observed Yorkie regulation by LKB1 and AMPK: the inactivation of LKB1 in the developing central nervous system induced the activation of Yorkie and a corresponding overgrowth of larval tissues, while LKB1 overexpression induced Yorkie inhibition through AMPK [56]. In line with observations in mammalian systems, AMPK was able to directly phosphorylate Yorkie in vitro.…”
Section: Involvement Of Lkb1: Insights From Drosophilasupporting
confidence: 66%
“…AMPK can phosphorylate AMOTL1, which in turn facilitates YAP phosphorylation by LATS1/2 (DeRan et al, 2014). A similar mechanism is also present in Drosophila , in which Ampk inactivates Yki and affects cell proliferation in the larval central brain and central nerve cord (Gailite et al, 2015). It appears that during energy stress, both AMPK and LATS1/2 are unleashed to restrict YAP activity.…”
Section: Effect Of Cellular Metabolic Status On Hippo Signalingmentioning
confidence: 86%
“…It is known to regulate the proliferation of two cell populations in the larval D. melanogaster brain: glia and the neuroepithelium [10][11][12]. Although the Yorkie (Yki) transcription co-activator was recently linked to neuroblast biology downstream of the Lkb1 and AMPK kinases [13], a role for the Hippo pathway core kinases in control of neuroblasts, the stem cell population that produces 90% of adult brain cells, has not been reported. To investigate the Hippo pathway in brain development, we surveyed expression of key Hippo pathway proteins in the third-instar larval brain using endogenously tagged alleles of the kinases tao-1 and hippo (hpo) and a Yki antibody ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%